2015
DOI: 10.1007/s11357-015-9759-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity and cognitive decline in older adults living in the community

Abstract: Accumulating evidence suggests that physical activity may be beneficial in preserving cognition in late life. This study examined the association between baseline and changes in physical activity and cognitive decline in community-dwelling older people. Data were from the Korean Longitudinal Study of Aging, with 2605 aged 65 years and older subjects interviewed in 2006 and followed up for 2 years. Cognitive decline was defined by calculating the Reliable Change Index using the Mini-Mental State Examination. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 46 publications
1
25
1
1
Order By: Relevance
“…The results of adjusted analysis indicated that there were no significant patterns in relations between physical activity and cognitive decline in any of the three states. These findings differed from previous research that showed physical activity to be a neuroprotective factor [1][2][3][4][7][8][9].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of adjusted analysis indicated that there were no significant patterns in relations between physical activity and cognitive decline in any of the three states. These findings differed from previous research that showed physical activity to be a neuroprotective factor [1][2][3][4][7][8][9].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, this study examined females ages 55 to 64, whereas most previous research focused on the elderly [1,[6][7][8]12]. The variables in this study were concurrent levels of cognitive decline and physical activity levels at one point in time; therefore, benefits of physical activity for cognitive decline may not be immediate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary objectives of studies have been and continue to be the evaluation and measurement of the cognitive benefits that PA can potentially confer with special attention to cognitively impaired individuals, including those with dementia [5, 6], Alzheimer’s disease [7], Parkinson’s disease [8, 9], schizophrenia [10], or mild cognitive impairment [11, 12]. Cognition has been measured along the domains of executive function, attention, memory, and working memory, each associated with distinct psychological measurement instruments.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Regular physical activity can lower the risk of mortality, cardiopathies 8 , strokes, hypertension, type II diabetes, osteoporosis, obesity, colon cancer and breast cancer. 2,11 Exercise also reduces anxiety, depression 12 , cognitive decline 13 and stress levels, and improves overall well-being and mental energy. 14,15,16 Physical activity programs have been suggested as a necessary course of action to promote healthy lifestyles and a better quality of life.…”
Section: Intr Intr Intr Intr Introduction Oduction Oduction Oduction mentioning
confidence: 99%